The Drosophila melanogaster BTB proteins bric à brac bind DNA through a composite DNA binding domain containing a pipsqueak and an AT-Hook motif - Lours, Corinne (Oxford University Press, 2003)
The bric à brac (bab) locus is composed of two paralogous genes, bab1 and bab2, in Drosophila melanogaster. Bab1 and Bab2 are nuclear proteins that contain a broad complex, tramtrack, bric à brac/poxviruses and zinc-finger (BTB/POZ) domain. Many BTB/POZ proteins are transcriptional regulators of which the majority contain C(2)H(2) zinc-finger motifs. There is no detectable zinc-finger motif in either Bab protein. However, they share the Bab conserved domain (BabCD) that is highly conserved between Bab1 and Bab2, and the Bab proteins of several other species, e.g. Anopheles gambiae, Apis mellifera and Drosophila virilis. Here we show that Bab2 binds to several discrete sites on polytene chromosomes including the bab locus, and that the BabCD of both Bab1 and Bab2 binds in vitro to the cis-regulatory regions of bab1 and bab2. Our results indicate that the BabCD binds to A/T-rich regions and that its optimum binding sites contain TA or TAA repeats. The BabCD is a composite DNA binding domain with a psq motif and an AT-Hook motif; both motifs are required for DNA binding activity. Structural similarities suggest that the BabCD may bind to DNA in a similar manner as some prokaryotic recombinases.